CCE Programme of States and Union Territories in India A Review - Sharma, Kavita (JOURNAL OF INDIAN EDUCATION, 2017)
With the implementation of the Right of Children to Free and Compulsory Education Act–2009, it became mandatory for the States and Union Territories (UTs) to implement Continuous and Comprehensive Evaluation (CCE) as mentioned in its Section 29(2). Since the Act aims at all-round development of children by enabling them to learn and progress in a fear- and anxiety-free environment therefore, while prohibiting any external examination till the elementary stage, it mandates using CCE as a school-based activity to ensure the right of each child to full-time elementary education of satisfactory and equitable quality. Post implementation of the RTE Act, almost all the States and UTs initiated steps in this direction, developed a variety of material on CCE and even implemented it in schools. To understand the extent to which the CCE schemes of the States/UTs incorporate and reflect the ethos of CCE, a review of the CCE material of 22 States/UTs was undertaken. This article is an attempt to highlight the strengths and gaps to help the States and UTs improve their CCE schemes and thus progress towards qualitative improvement of elementary education as envisaged under RTE Act.